2012
DOI: 10.1080/ac.67.6.2184671
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the left ventricular regional function using two-dimensional speckle tracking echocardiography in patients with end-stage renal disease with preserved left ventricular ejection fraction

Abstract: In patients with ESRD, although the longitudinal and radial systolic functions are reduced, the LVEF may remain within normal limits due to the preservation of the circumferential functions. 2D-STE has the potential to detect the severity of uraemic cardiomyopathy in the early stages of the disease and might provide useful information for the risk stratification in ESRD patients with PLVEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Even though decreases in longitudinal and radial systolic function have been reported in patients with ESRD, their LVEF may remain within normal range through preserved circumferential function. 2D speckle-tracking echocardiography has also been used to assess the severity of uremic cardiomyopathy during the early stages of the disease, and it may also be useful in patients with ESRD and preserved LVEF [40].…”
Section: ) Association Between Gls and CV Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though decreases in longitudinal and radial systolic function have been reported in patients with ESRD, their LVEF may remain within normal range through preserved circumferential function. 2D speckle-tracking echocardiography has also been used to assess the severity of uremic cardiomyopathy during the early stages of the disease, and it may also be useful in patients with ESRD and preserved LVEF [40].…”
Section: ) Association Between Gls and CV Outcomesmentioning
confidence: 99%
“…In addition, 2D speckle-tracking echocardiography has also been used to differentiate between active and passive myocardial motion to allow for the 2D angle-independent quantification of myocardial deformation, which can more accurately reflect the systolic and diastolic performance of all myocardial segments. GLS, which can be measured from 2D speckle-tracking echocardiography, is a novel method that has recently been used to assess systolic LV function [39], and less negative GLS has been reported to be associated with an increased risk of mortality in patients undergoing HD [40].…”
Section: Global LV Longitudinal Systolic Strain (Gls)mentioning
confidence: 99%
“…Other authors also reported LV ejection fractions that were in the normal range, but significantly lower than control, whereas other authors did not report such findings . However, altered systolic function may be detected by exercise echocardiography or strain using speckle tracking in CKD children on dialysis, despite the finding of a preserved ejection fraction …”
Section: Discussionmentioning
confidence: 93%
“…Although longitudinal and radial systolic functions are decreased in patients with ESRD, LVEF may remain within normal limits due to the preservation of circumferential function. 2D speckle-tracking echocardiography may be able to detect the severity of uremic cardiomyopathy in the early stages of disease, it may also be able to provide useful information for assessing risk in patients with ESRD with preserved LVEF [44]. Therefore, the use of GLS in maintenance HD patients may help to identify those at a high risk of poor outcomes.…”
Section: Discussionmentioning
confidence: 99%